Mathematics simulation and experiments of continuous casting with strip feeding in mold - M. G. Shen; Z. S. Zang; K. P. Shu (Metalurgija, 2017)
Steel strip feeding technology can reduce the degree of superheat of the molten steel, change the solidification order of the molten steel; raise the equiaxed crystal rate of the slab and improve the continuous casting quality. The paper establishes the mathematical model of heat transfer and temperature field of casting billet of steel strip feeding in continuous casting mold. Results show that if Plate Billet is 1 000 mm × 220 mm and the steel strip is 100 mm × 3 mm, feeding position of parallel is 250 mm from the narrow side. When the feeding speed is 3,6 m/min, the superheat degree can be reduced by 5 °C, and the solidification length can be reduced by 2,9 m. When the feeding speed is 6 m/min, the superheat degree can be reduced by about 9 °C, and the solidification length can be reduced by 3,7 m. The results of the test in a steel plant are in good agreement with the experimental results.